Sustainable coastal reclamation for community welfare in Bangkalan Regency, Madura Island, East Java - I Gusti Ayu Gangga Santi Dewi; Bambang Eko Turisno (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
Rapid population growth and the market expansion in various sectors in Bangkalan Regency have contributed to a rise in land demand. Therefore, the creations of new areas through land/coastal reclamation projects are taken place in this region. Based on this phenomenon, this study aims to analyze the potential and benefits of reclamation in Bangkalan Regency. The study uses a socio-legal approach and is a field research with verstehen (hermeneutic) approach. Data were obtained from informants, especially residents who have benefited from reclaimed land, village apparatus, and related agencies. Data were analyzed using triangulation technique. The results of the study found that in Bangkalan Regency, tourism in reclaimed land involves coastal communities, including fishermen, to manage the area, and it can improve community welfare. Furthermore, reclaimed land is used to expand their current land for settlement and business, as well as for the development of natural resource conservation such as mangroves and fish ponds. Reclaimed land in Bangkalan Regency is used for tourist destinations and settlement areas for the communities with their business.